Structure of Polyaniline and Its Influences on the Electrochemical Performance of LiCoO2 Cathode for Lithium Ion Batteries - Zeng, Liancheng; Fan, Changling (Asian Journal of Chemistry, 2013)
Polyaniline synthesized by chemical polymerization is replace acetylene black to be used as the conductive additive of LiCoO2 cathode. FTIR shows that polyaniline prepared possesses the typical features of conductive emeraldine salts. The conductivity of polyaniline is 15.29 S cm-1 which is more than that of acetylene black. Polyaniline has some discharge capacity in the potential range of cathode, so it can be used as the cathode material. The conductivity changes of LiCoO2 cathode film with the increase of the content of conductive additive conform to the percolation theory. The conductivity of cathode reaches its maximum value of 4.02 × 10-1 S cm-1 when the content of polyaniline reaches 15 wt. %, which is much bigger than that of acetylene black. The electrochemical performances of LiCoO2 cathode is improved remarkably. The discharge capacity of LiCoO2 cathode is 95.9 mAh g-1 at the current density of 170 mA g-1. Its charge transfer resistance is much lower than that of acetylene black in the 20 cycle. The resilience of polyaniline reduces the expansion and contraction of LiCoO2, which keeps the conductive network integrity.